2012
DOI: 10.1177/0961203312458838
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune/inflammatory syndrome (ASIA) induced by biomaterials injection other than silicone medical grade

Abstract: Infrequently, biomaterials other than silicone can provoke local inflammatory adverse reactions that may evolve into systemic autoimmune and/or granulomatous disorders. Whether or not these biomaterials act as an adjuvant, they could be included in the ASIA category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 30 publications
0
31
0
9
Order By: Relevance
“…Alijotas-Reig et al observed that 15 out of 185 cases (8%) of patients suffering from inflammatory/autoimmune disorders related to bioimplant injections had systemic or distant and multiple complaints that could be categorized as ASIA. SS was diagnosed in two patients representing a rather infrequent yet possible manifestation following a chronic stimulation from biomaterials used as fillers [ 89 ], an evidence reinforced by a further 3 cases published later on [ 90 ]. Thus, the epidemiology and pathomechanisms possibly linking some agents acting as adjuvants such as vaccines, silica, silicone implants and other biomaterials with SS are yet to be clarified.…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%
“…Alijotas-Reig et al observed that 15 out of 185 cases (8%) of patients suffering from inflammatory/autoimmune disorders related to bioimplant injections had systemic or distant and multiple complaints that could be categorized as ASIA. SS was diagnosed in two patients representing a rather infrequent yet possible manifestation following a chronic stimulation from biomaterials used as fillers [ 89 ], an evidence reinforced by a further 3 cases published later on [ 90 ]. Thus, the epidemiology and pathomechanisms possibly linking some agents acting as adjuvants such as vaccines, silica, silicone implants and other biomaterials with SS are yet to be clarified.…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%
“…5 These clinical and laboratory features related to exposure to diverse external stimuli were also studied by Shoenfeld and were identified as 'ASIA' or autoimmune/inflammatory syndrome induced by adjuvants. 6,7 So fillers can induce not only autoimmunity, but also, in a few cases, welldefined autoimmune diseases like, in our case, SLE. Considering the increasing use of fillers in general and PAI in particular, physicians should be aware of the risks of this potentially important clinical problem.…”
mentioning
confidence: 73%
“…There may be some debate as to whether any silicone-related reaction is always an acquired entity or whether some may have crossreactive or direct immune reactions that are stimulated after non-specific polyclonal activation for other reasons. Whereas silicone has drawn much attention in the ASIA context, various non-silicone adjuvants have also been associated with similar immune activations [61][62][63][64][65][66][67][68]. These include in the least acrylates, hyaluronic acid derivatives, acrylamides, poly-L-lactic acid, dental amalgams, various skin fillers, and vaccine components.…”
Section: Autoimmune/inflammatory Syndrome Induced By Adjuvantsmentioning
confidence: 99%
“…The clinical symptoms and signs of ASIA are considerably diverse (Tables 1, 2, and 3) [6,7,50,52,66,68,[71][72][73][74][75]. Most of the information in this regard is borrowed from the experience of ASIA and breast implants, although the clinical data relating to other foreign body materials is expanding.…”
Section: Autoimmune/inflammatory Syndrome Induced By Adjuvantsmentioning
confidence: 99%